Global Prevalence of Colistin Resistance in Klebsiella pneumoniae from Bloodstream Infection: A Systematic Review and Meta-Analysis - Leonard Ighodalo Uzairue; Ali A. Rabaan; Fumilayo Ajoke Adewumi; Obiageli Jovita Okolie; Jamiu Bello Folorunso; Muhammed A. Bakhrebah; Mohammed Garout; Wadha A. Alfouzan; Muhammad A. Halwani; Aref A. Alamri; Shaima A. Halawani; Fatimah S. Alshahrani; et al. (Pathogens, 2022)
Background: Among gram-negative bacteria, Klebsiella pneumoniae is one of the most common causes of healthcare-related infection. Bloodstream infections (BSIs) caused by Klebsiella pneumoniae are notorious for being difficult to treat due to resistance to commonly used antimicrobials. Klebsiella pneumoniae isolates from bloodstream infections are becoming increasingly resistant to carbapenems. In the fight against carbapenem-resistant Klebsiella pneumoniae, colistin [polymyxin E] is the antimicrobial of choice and is thus widely used. Objective: This study aimed to determine the global prevalence of colistin resistance amongst Klebsiella pneumoniae isolates from bloodstream infections. Methods: PubMed, Medline, Scopus, and the Cochrane Library were searched for published articles without restricting the search period. Studies meeting the predefined inclusion and exclusion criteria were included, and quality was assessed using Joanna Briggs Institute Checklist. We used a statistical random effect model to analyze data with substantial heterogeneity (I2 > 50%) in the meta-analysis. Results: A total of 10 studies out of 2873 search results that met the inclusion criteria were included in the final synthesis for this study. A pooled prevalence of colistin resistance was 3.1%, 95% CI (1.5–4.7%). The highest colistin resistance pooled prevalence was recorded in isolates studied in 2020 and beyond 12.90% (4/31), while Klebsiella pneumoniae isolates studied in 2015 and before and in 2016–2019 showed a pooled colistin resistance rate of 2.89% (48/1661) and 2.95% (28/948), respectively. The highest colistin resistance was found in Klebsiella pneumoniae isolates from Thailand (19.2%), while the least pooled resistance was in Klebsiella pneumoniae from South Korea (0.8%). The pooled prevalence of the multidrug-resistant (MDR) of Klebsiella pneumoniae from bloodstream infection ranged from 80.1%, 95% CI (65.0–95.2%), and the resistance prevalence of other antibiotics by Klebsiella pneumoniae from bloodstream infections were as follows; ciprofloxacin (45.3%), ertapenem (44.4%), meropenem (36.1%), imipenem (35.2%), gentamicin (33.3%), amikacin (25.4%) and tigecycline (5.1%). Klebsiella pneumoniae recovered from the intensive care unit (ICU) showed higher colistin resistance, 11.5% (9/781%), while non-ICU patients showed 3.03% (80/2604) pooled colistin resistance. Conclusion: This study showed low colistin resistance in Klebsiella pneumoniae isolates from global bloodstream infections. However, significant colistin resistance was observed in isolates collected from 2020 and beyond. Significant colistin resistance was also observed in Klebsiella pneumoniae isolates in bloodstream infections from the intensive care unit (ICU) compared to those from non-ICUs. As a result, there is a need to institute colistin administration stewardship in the ICU in clinical settings.